A literatura juvenil brasileira no início do século XXI: autores, obras e tendências - Gabriela Luft (Estudos de Literatura Brasileira Contemporânea)
The present research offers a study on Brazilian youth literature published in the first decade of this century, by analyzing the books awarded by National Foundation of Children’s and Youth Books, and Brazilian Book Chamber, which awards the prize Jabuti. Based on systematized data by Marisa Lajolo and Regina Ziberman, it shows a brief overview of Brazilian children’s and youth literature from 1890 to 1980, the context of which allows tracing the paths and trends of the genre over time. After that, based on studies developed by Teresa Colomer, this study discusses the main features of the current juvenile narratives awarded from 2001 to 2009. Through reading, observation, analysis and comparison of works that make up the corpus, this research aims to show the characteristics of the Brazilian youth literature produced in the first decade of the XXI century, in order to answer what are the main trends of the genre and what is its position in the national scenery. We can observe a number of new authors who have turned up, the diversity of themes worked, and the increase of the narrative complexity.